2008
DOI: 10.1007/s00213-008-1122-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced reinstatement of cocaine seeking is mediated by the kappa opioid system

Abstract: Introduction-Prior activation of the kappa opioid system by repeated stress or agonist administration has been previously shown to potentiate the rewarding properties of subsequently administered cocaine. In the present study, intermittent and uncontrollable footshock, a single session of forced swim, or acute administration of the kappa agonist U50,488 (5 mg/kg) were found to reinstate place preference in mice previously conditioned with cocaine (15 mg/kg) and subsequently extinguished by repeated training se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
197
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(213 citation statements)
references
References 55 publications
14
197
2
Order By: Relevance
“…Recent evidence supports a critical role of KOR in stress-induced reinstatement to drug seeking (6,7), but the sites of action in brain responsible and the relationship between KOR-dependent aversion and reinstatement are not clear. Animals injected with norBNI or saline in DRN showed equivalent cocaine place preference (CPP) after three training sessions and showed no differences in cocaineinduced locomotor activity during the training sessions (Fig.…”
Section: Kappa-opioid Receptors In the Drn Mediate Aversion And Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence supports a critical role of KOR in stress-induced reinstatement to drug seeking (6,7), but the sites of action in brain responsible and the relationship between KOR-dependent aversion and reinstatement are not clear. Animals injected with norBNI or saline in DRN showed equivalent cocaine place preference (CPP) after three training sessions and showed no differences in cocaineinduced locomotor activity during the training sessions (Fig.…”
Section: Kappa-opioid Receptors In the Drn Mediate Aversion And Drugmentioning
confidence: 99%
“…Corticotropin releasing factor (CRF) orchestrates the complex endocrine and neuronal responses to behavioral stress exposure (4), and recent studies have suggested that the dysphoric properties of stress are encoded by CRF-induced activation of the endogenous dynorphin opioid system (5). Systemic administration of kappa opioid receptor (KOR) antagonists block the aversive (5) and pro-addictive effects of stress (6)(7)(8)(9), and dynorphin activation of KOR is thought to mediate opponent processes evoked by addictive drugs (10), yet the key sites of dynorphin/KOR action mediating these behavioral responses are not resolved.…”
mentioning
confidence: 99%
“…Studies correlating the dysphoric effects of ÎșOR agonists to the G-protein-independent activation of the p38 MAPK pathway (8,13,15) suggest that identification of ÎșOR agonists biased to G-protein-mediated signaling could lead to the development of therapeutics with reduced side effects. This suggestion has spurred the search for novel ÎșOR ligands or scaffolds that could provide novel treatment strategies for a variety of disorders where ÎșOR involvement has been implicated (16,17).…”
mentioning
confidence: 99%
“…[69][70][71] Similarly, several studies have shown that stress exposure induces the reinstatement of opioid-, amphetamine-, cocaine-, and nicotine-induced CPP. 64,[71][72][73][74] There is reasonable evidence to support the face validity of the reinstatement model, but neither its predictive validity nor its functional equivalence have been fully established. 60 …”
Section: Animal Studies Of Addictive Behaviormentioning
confidence: 99%